Evaluating the Efficiency of Tax Liability Calculations under PP No. 23/2018: A Tax Planning Perspective for PT. X - Elmanizar, Elmanizar; Murtadho, M. Akmal (E-Jurnal Akuntansi; Vol 34 No 10 (2024)DO - 10.24843/EJA.2024.v34.i10.p04, 2024)
This study examines the tax planning strategies implemented by PT. X in 2023, focusing on the extent to which these strategies enhance efficiency by minimizing taxes payable. The research employs a descriptive qualitative approach, utilizing a case study model that centers on a single taxpayer, PT. X. Data collection involves documentation, with the company’s financial reports serving as the primary source of secondary data. The analysis involves calculating the tax payable under applicable tax regulations and comparing it to the tax liability in the absence of a business split. This comparison allows for an evaluation of the effectiveness of the tax planning measures adopted by the company. Findings indicate that the tax planning strategy of undertaking a business split aligns with the spinoff provisions outlined in Law No. 40/2007. This approach has demonstrated tangible efficiency in reducing tax liabilities, as the newly formed entities can leverage the favorable tax rate provided under PP No. 23/2018. The results underscore the strategic value of adhering to regulatory frameworks to achieve tax efficiency.